Creation and Investigation of a Big Data Technology-Driven Auxiliary Employment Platform for Public Utilities Management - Lan, Zhijie (Bright Institute, 2023)
With the development of society and the advancement of science and technology, the current employment problem has gradually become hotter. At the same time, the number of college graduates has shown rapid growth. However, due to the development of science and technology in our country, the demand for labor has declined, and various factors have caused college students to find themselves in a difficult situation.The purpose of this article is to conduct research on the design of a public utility management assisted employment platform based on big data technology. Based on the analysis of the employment history and current situation of college students in New China, this paper analyzes the employment dilemma of college students from the perspective of